1983
DOI: 10.1016/s0022-5347(17)52619-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased Urinary Excretion of Renal Enzymes in Idiopathic Calcium Oxalate Nephrolithiasis

Abstract: Urinary excretion of gamma-glutamyl transpeptidase, angiotensin I converting enzyme, beta-galactosidase and N-acetyl-beta-glucosaminidase was evaluated in 30 patients with idiopathic calcium oxalate urolithiasis. Higher than normal values were observed and the excretory enzyme pattern suggested tubular damage in patients with stones. A parallel study in the rat showed that an oxalate surcharge can promote increased urinary excretion of these enzymes. It is known that urothelium injury may enhance crystal adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
2

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 5 publications
4
44
0
2
Order By: Relevance
“…Human urine contains type IV collagenase (42), NAG, cathepsins L and B (22,52), cathepsin H (52), alkaline phosphatase, leucine aminopeptidase, and ␥-glutamyl transpeptidase (22). The activities of NAG and ␤-galactosidase (3,21) and also those of ␣-glucosidase and ␥-glutamyl transpeptidase (3) are elevated in urine from stone patients, as is the level of an unidentified serine protease that cleaves OPN (4). Similar changes accompany nephrocalcinosis induced in hyperoxaluric rats (24,25,56), in which COM crystal formation is associated with significant, proportional increases in urinary oxalate and activity of NAG and the brush-border enzymes alkaline phosphatase, leucine aminopeptidase, and ␥-glutamyl transpeptidase (24,25,56).…”
Section: Discussionmentioning
confidence: 99%
“…Human urine contains type IV collagenase (42), NAG, cathepsins L and B (22,52), cathepsin H (52), alkaline phosphatase, leucine aminopeptidase, and ␥-glutamyl transpeptidase (22). The activities of NAG and ␤-galactosidase (3,21) and also those of ␣-glucosidase and ␥-glutamyl transpeptidase (3) are elevated in urine from stone patients, as is the level of an unidentified serine protease that cleaves OPN (4). Similar changes accompany nephrocalcinosis induced in hyperoxaluric rats (24,25,56), in which COM crystal formation is associated with significant, proportional increases in urinary oxalate and activity of NAG and the brush-border enzymes alkaline phosphatase, leucine aminopeptidase, and ␥-glutamyl transpeptidase (24,25,56).…”
Section: Discussionmentioning
confidence: 99%
“…Increased excretion of cellular enzymes has been observed in the urine of stoneforming humans (18,19) and of oxalate-loaded rats (20), and it has been postulated that cellular damage could result from crystal deposition. However, when the nephrotoxin gentamycin was administered to rats together with oxalate, crystal deposition was enhanced (31), suggesting that cellular damage might precede and promote crystal retention, rather than be a consequence of the crystals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies in stoneforming humans (18,19) and oxalate-loaded rats (20) have demonstrated that renal cellular injury occurs. In the current study, we defined the effect of diverse injuries to renal cells on crystal adhesion and how the PGE system might modulate this response.…”
mentioning
confidence: 99%
“…Crystal retention could be caused by adherence of crystals to the epithelial cells lining the renal tubules (2). Although many investigators recognized a role for renal tubular injury in the pathophysiology of nephrolithiasis, definite proof for this concept and the mechanisms involved are not yet available (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%